The Historical Evolution of Traditional Wearable Epidemic Prevention Methods in Ancient China - Xiong XIAO (Yixue yu zhexue)
The traditional wearable epidemic prevention methods in ancient China were influenced by folk beliefs and medical thoughts in the process of historical development. By analyzing relevant records in ancient literature, this paper proposes a periodization using the Song Dynasty as a key dividing line. Before the Song Dynasty, these methods retained more primitive thinking, relying heavily on items symbolically believed to ward off epidemics, influenced by the folk concept of "epidemic ghost view" and religious epidemic prevention practices. After the Song Dynasty, with the widespread use of aromatic medicinal substances and a deeper medical understanding of epidemics, these methods reflected a greater degree of medical rationality. The historical evolution of traditional wearable epidemic prevention methods reveals a transition from the close integration of medical thought and folk belief to their gradual separation. This evolution offers insights into how such traditional practices can be better applied in modern contexts.